Subjective Memory Change, Mood, and Cerebrovascular Risk Factors in Older African Americans. (November 2017) - Sperling, Scott A.; Tsang, Siny; Williams, Ishan C.; Park, Moon Ho; Helenius, Ira M.; Manning, Carol A.
Objective: Subjective memory change (SMC) in older individuals may represent a harbinger of cognitive decline. This study examined the factors associated with SMC in older African Americans (AA), who have greater risk of developing dementia. We predicted that symptoms of depression and anxiety, as well as the total number of cerebrovascular risk factors (tCVRFs), but not performances on objective memory measures, would be positively associated with SMC. Methods: Ninety-six AA completed brief cognitive testing and answered questions about mood and memory at their primary care appointment. Vascular data were obtained from medical records. Results: Symptoms of depression and anxiety, but not performances on objective memory measures, were positively associated with SMC, t (χ 2 (1) = 16.55 and 12.94, respectively, both P < .001). In nondepressed participants, the tCVRF was important in distinguishing between those with and without SMC. Conclusions: In older AA, symptoms of depression or anxiety were associated with SMC. In nondepressed AA, the tCVRFs were important in distinguishing between those with and without SMC.